Antiproliferative effects of bioaccessible fractions of honeys from Sicilian black honeybee (Apis mellifera ssp. sicula) on human colorectal carcinoma cells. (10th June 2021) - Cilla, Antonio; López‐García, Gabriel; Barberá, Reyes; Frazzitta, Anna; Restivo, Ignazio; Tesoriere, Luisa; Attanzio, Alessandro
Summary: The aim of this study was to evaluate the antiproliferative activity of bioaccessible fractions (BFs) obtained by the internationally standardized INFOGEST static digestion method to Sicilian honeys of three distinct floral origins (Sulla, Thistle and Dill) and the Manuka honey (gold standard), and to compare their effects based on total polyphenol content (TPC). Differentiated CaCo‐2 cells (intestinal‐like) and non‐differentiated CaCo‐2 and HCT‐116 colonic tumour‐like cells were incubated for 24 h with BFs of honeys to test viability, apoptosis, mitochondrial membrane potential (MMP), ROS and cell cycle. TPC after digestion ranked in the following order: Dill > Thistle > Sulla > Manuka. No decrease in cell viability in differentiated CaCo‐2 cells was observed, while a reduction to 25–85% (CaCo‐2) and 20–80% (HCT‐116) of viability was obtained. This descent in viability was caused by a cell cycle block with an increase in apoptosis through dissipation of MMP and raise in ROS levels, being Thistle and Dill the most effective honeys followed by Sulla and finally Manuka, in agreement with TPC after digestion. Abstract : Antiproliferative effects of bioaccessible fractions of honeys from Sicilian black honeybee ( Apis mellifera ssp. sicula ) on human colorectal carcinoma cells.